Motivation of Employees in Health Care - Krejčová, Petra; Pauknerová, Daniela, 1970-; Lukeš, Martin, 1976-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
The main aim of this thesis is to analyse and discuss selected aspects of Czech healthcare environment and their influence on motivation and job satisfaction of doctors. The hypotheses and assumptions based on the analyses in the theoretical part were tested in the form of detailed employee satisfaction questionnaire research conducted in Hospital Prachatice, a small healthcare facility in South Bohemia. Even though the overall situation in Czech healthcare is rather escalated and bitter, the results of the research were better than expected and showed that the new hospital management is working hard on improving the relationships, communication with medical personnel, as well as overall situation in Hospital Prachatice. Even though there is still a long way ahead of them, they seem to be moving in the right direction.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses